Kerangka Konseptual Model Pembelajaran Real Math Literacy (RML) - Angriani, Andi Dian; Tampa, Alimuddin (Al asma : Journal of Islamic Education, 2025)
One of the most important competencies in the 21st century is mathematical literacy. However, the importance of mathematical literacy has not been in line with the achievements of Indonesian students, who are still relatively low. One of the reasons is that the learning model used to manage activities in the classroom has not been maximized. The writing of this article provides an overview of the development of Real Math Literacy (RML) learning model components consisting of syntax, social system, reaction principles, support system, instructional impact, and accompanying impact. Real Math Literacy (RML) learning model designed is the result of analysis, elaboration, and synthesis of relevant learning theories, the main components underlying mathematical literacy, the discovery learning model, and assessment for learning. Real Math Literacy (RML) learning model is expected to be a practical alternative for educators in designing learning processes that can improve students’ mathematical literacy.